Coping Mechanisms among Women Who Experience Dysmenorrhea in Baleasri Village, Magetan, Indonesia - Tassyabela, Fadia Meisyn; Sunarto, Sunarto; Sulikah, Sulikah; Surtinah, Nani (Knowledge Dynamics, 2024)
Background: Dysmenorrhea (menstrual pain) is often experienced by women of childbearing age. The main complaint is abdominal pain that spreads from the lower back to the thighs. The pain complaint results in disruption of daily activities. The purpose of the study was to identify the description of type of coping, and coping mechanisms in women who experience dysmenorrhea. Methods: The type of research used was descriptive exploratory with a population of 252 women of childbearing age who experienced dysmenorrhea. The sample size of this study was 152 women (Krejci & Morgan table). The independent variable is dysmenorrhea, and the dependent variable is the type and coping mechanisms. The instrument for identifying the type, and coping mechanisms used a questionnaire. Data on women of childbearing age who experienced dysmenorrhea were obtained from secondary data from the Village Midwife's records. Data collection techniques used questionnaires and secondary data observations. Data analysis was carried out descriptively, in the form of frequency distribution percentages and prevalence ratios. Results: The results showed that women who experienced dysmenorrhea tended to use adaptive coping. The most frequently used coping mechanism was problem-focused coping. Women who work and are active in sports are risk factors that can reduce dysmenorrhea. Adolescent age, secondary education, age of menarche less than 12 years, and menstrual periods more than 7 days are triggers for dysmenorrhea. Conclusion: regular exercise and work are positive coping mechanisms that can reduce dysmenorrhea.